B vitamins in diseases of the nervous system - facts and myths - Jasłowski, Damian (Journal of Education, Health and Sport, 2023)
Introduction: B vitamins are necessary for the proper functioning of the nervous system, taking part in the synthesis of neurotransmitters, RNA and DNA and acting as cofactors in many cellular metabolic pathways. The body does not store them, so they need to be replaced daily. Mild deficiencies can cause non-specific neuropsychiatric disorders, and deep and persistent - serious, fatal disease states that require intensive supplementation, such as beriberi disease or Korsakoff’s syndrome. Materials and methods: My work is based on the articles published in PubMed, medical books and websites. I was looking for the key words such as ‘biotin‘, ‘brain’, ‘homocysteine’, ‘niacin’, ‘pantothenic acid’, ‘riboflavin’, ‘thiamin’, ‘neuropathy’. Results: B vitamins seem to enhance the analgesic effect of NSAIDs. There is evidence of supportive action in the treatment of low back pain and diabetic neuropathy. There is no reliable evidence of improved cognitive function in patients with Alzheimer’s disease or other types of dementia. Conclusions: due to the low toxicity, very few side effects and experimental findings, it seems reasonable to administer B vitamins in numerous pain syndromes, such as neuropathies and back pain syndromes. However, we need more randomized clinical trials to create universal recommendations and finally confirm the positive effects of these substances in neurological diseases.